Construction of multifunctional dual Z-scheme composites with enhanced photocatalytic activities for degradation of ciprofloxacin. (15th June 2021) - He, Zuming; Yang, Hanpei; Su, Jiangbin; Xia, Yongmei; Fu, Xiaofei; Wang, Lina; Kang, Li
Graphical abstract: Proposed mechanism of the photoproduced charge transfer in 75NBA composite under visible-light irradiation. Highlights: Novel multifunctional dual Z-scheme NiFe2 O4 /Bi2 WO6 /AgI composite is constructed. The heterostructure exhibits enhanced electron-hole separation by dual Z-scheme channel pathway. NiFe2 O4 /Bi2 WO6 /AgI can also highly efficiently degrade CIP. The in-depth mechanisms insight of charge separation. Abstract: Visible-light-driven (VLD) photocatalysis has aroused extensive attention due to their great potential in applications concerning energy crisis and environmental pollution. Hence, for the first time, VLD and magnetic recyclable dual Z-scheme NiFe2 O4 /Bi2 WO6 /AgI (NBA) composites were prepared via a hydrothermal method to obtain NiFe2 O4 /Bi2 WO6 (NB) following an in situ deposition of AgI. The as-prepared NBA catalysts exhibit excellent photocatalytic performance for the degradation of ciprofloxacin (CIP) compared to the pristine NiFe2 O4, Bi2 WO6 or AgI under visible-light (VL) illumination. Among them, the 75%NiFe2 O4 /Bi2 WO6 /AgI (75NBA) composite exhibits optimal photocatalytic efficiency, which is 1.67, 1.51, 1.83 times higher than those of the pristine NiFe2 O4, Bi2 WO6 and AgI within 60 min, respectively. The high catalytic efficiency may be ascribed to the synergistic effect of the increased VL harvesting and dual Z-Scheme transmission paths in 75NBA system. Furthermore, trapping experiments and electrochemical impedance spectroscopy (ESR) analysis verify the co-existing of OH and O2 − in the 75NBA photocatalytic system. Additionally, the magnetic 75NBA can be rapidly separated from water by an external magnet. Based on the results from High performance liquid chromatography-mass spectrometry (HPLC-MS) analysis, four path ways towards the degradation of CIP are proposed. The highly efficient photocatalytic activity and magnetically reproducibility suggest that it is expected to be used in antibiotic wastewater treatment.